Gender and the Choice of a Science Career: The Impact of Social Support and Possible Selves. - Buday, Sarah; Stake, Jayne; Peterson, Zoë (Sex Roles, 2012)
This study examined the relationships among perceived social support, beliefs about how one would fare in a science career, and perceptions and choice of a career in science. Participants were 48 men and 33 women from the Midwestern United States who had been identified as gifted in mathematics and science and participated in a high school science enrichment program. They ranged in age from 24 to 28 years old, and the sample was predominantly White (83.3%). Participants completed an online measure approximately 10 years after the program ended examining their sources of support and beliefs about the self as a scientist to see how these variables influence perceptions of a science career and actual career. We expected that the relationship between perceived support from people and current job held would be mediated by participants' beliefs about their personal life as a scientist in the future. Similarly, we expected that the relationship between a perceived supportive environment and having a science career would be mediated by participants' beliefs about their career as a scientist in the future. Findings indicated that social support contributed directly to men's and women's ability to envision themselves in a future science career, which, in turn, predicted their interest in and motivation for a science career. No significant gender differences were found in the predictors of men's and women's perceptions and choice of a science career. Implications for recruitment of students into scientific majors and careers are discussed.